Analysis of catches data collection system at Fish Landing Base (PPI) of Dumai - Ratu Sari Mardiah; Sri Yenica Roza; Edy Miswar (Depik, 2021)
Data collection system in Fish Landing Base of Dumai was traditionally. Data written manually using books and collected by agents. This fact illustrates the weakness of the catch data collection system that occours. The effect is low data accuracy and requires a longer time in reporting. Data collection system based on technology will facilitate the process and important to do. The purpose of this study was to design a data collection system for fish catches landed at Fish Landing Base of Dumai. The research was conducted in February-June 2020 in Dumai city. The method used observation, interviews and literature review. Data analysis is used the process of analyzing data, literature review, analysis of existing systems, analysis of new systems and system design using data flow diagrams (DFD), entity relationship diagrams (ERD) and HIPO. System design starts from input, output and database design. The data design inputted is fishermen data, fishing gear, fish production and price of day, fish distribution, customer data and data employees. The output data are reports of user data, fishing gear specifications, fish production and fish distribution. The database is structured and presented using a flow chart. A technology-based of catch data collection system designed to improve the efficiency of the presentation of the reports needed for agencies.Keywords:Fish LandingDFDReportAgencies